Kajian Potensi Pengunjung dalam Rangka Pengembangan Bisnis Wisata Alam (Studi Kasus Wisata Alam Kumkum di Kota Palangka Raya): Study of Visitor Potential in the Context of Nature Tourism Business Development (Case Study of Kumkum Nature Tourism in Palangka Raya City) - Shofiyah, Shofiyah (Anterior Jurnal, 2023)
Study of Visitor Potential in the Context of Nature Tourism Business Development (Case Study of Kumkum Nature Tourism in Palangka Raya City)